2021
DOI: 10.18502/cmm.6.4.5441
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus flavus endocarditis and meningitis in a child with marfan syndrome

Abstract: Background and Purpose: Aspergillus species are implicated as the etiology of approximately 26% of endocarditis cases. Central nervous system aspergillosis is a life-threatening condition that has a mortality rate of 80%. Case report: Herein, we report a four– year- old female who was admitted to the pediatric infectious ward due to a fever of unknown origin in January 2020. She was a known case of Marfan syndrome with a family history of this syndrome in her mother. The species was identified using (PCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Previously, the initial treatment of choice for IA affecting the CNS was systemic antifungal treatment with AMB, but now guidelines have switched to VCZ as the initial treatment, given that VCZ is more capable of reaching the proper concentration required for antifungal activity in the CSF. It also has lower toxicity potential compared with AMB 1,9 . Also, ICZ and isavuconazole (ISZ) were used in some previous cases; Tattevin et al reported 3 patients with neuroaspergillosis and underlying diseases, receiving ICZ in combination with other agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, the initial treatment of choice for IA affecting the CNS was systemic antifungal treatment with AMB, but now guidelines have switched to VCZ as the initial treatment, given that VCZ is more capable of reaching the proper concentration required for antifungal activity in the CSF. It also has lower toxicity potential compared with AMB 1,9 . Also, ICZ and isavuconazole (ISZ) were used in some previous cases; Tattevin et al reported 3 patients with neuroaspergillosis and underlying diseases, receiving ICZ in combination with other agents.…”
Section: Discussionmentioning
confidence: 99%
“…It also has lower toxicity potential compared with AMB. 1 , 9 Also, ICZ and isavuconazole (ISZ) were used in some previous cases; Tattevin et al reported 3 patients with neuroaspergillosis and underlying diseases, receiving ICZ in combination with other agents. One of the patients (a known case of wegener granulomatosis) was cured with AMB (29 days) + ICZ (410 days), another individual (suffering from laryngeal cancer) receiving AMB (25 days) + ICZ (13 days) died, and the last one (a case of systemic lupus erythematosus and end‐stage renal disease) was cured by receiving liposomal AMB (44 days) + VCZ and ITZ (380 days).…”
Section: Discussionmentioning
confidence: 99%